Influence of different pig genotype on aroma, colour and fatty acid composition of smoked dry-cured ham - Marušić, Nives, inženjerka prehrambene tehnologije (Array, 2019)
The aim of this study was to determine the influence of different genotypes of pigs ((Landrace x large Yorkshire) x Duroc (LYD) and Black Slavonian (BS) pig) on the colour, fat content and fatty acid composition of smoked dry-cured ham and identify volatile aroma-active compounds. The fat content was determined by applying the Smedes method and the composition of fatty acids by using the gas chromatography, while volatile aroma-active compounds were investigated by using the headspace-solid phase microextraction (HS-SPME) and the gas chromatography-mass spectrometry (GC-MS). Different genotypes of pigs did not show a statistically significant difference (p>0.05) in total fat content, but there was a difference in the proportion of individual fatty acids. We identified a total of 103 volatile compounds belonging to the following groups of chemical compounds: 19 aromatic hydrocarbons, 17 aliphatic hydrocarbons, 17 ketones, 15 phenols, 14 aldehydes, 11 alcohols, 5 acids, 2 terpenes and 1 sulphur compound. The most abundant chemical groups of compounds in samples of smoked dry-cured ham from LYD pigs were aldehydes, phenols and aromatic hydrocarbons, while the most abundant chemical groups of compounds in samples of smoked dry-cured ham of BS genotype were phenols, aldehydes and alcohols.